KEWENANGAN PENGADILAN AGAMA DALAM MENGADILI PERCERAIAN YANG DISEBABKAN PERPINDAHAN AGAMA (MURTAD) SEORANG SUAMI (STUDI PUTUSAN NOMOR: 603/PdtG/2014/PA.MDN) - VITA RISKY (PREMISE LAW JURNAL, 2016)
Religious Court is only allowed to process a divorce if one of the parties files an application or claim to divorce. If the marriage is conducted and registered in Islamic way, its break can be carried out by the Religious Court. The research used normative judicial method with descriptive analysis which approaches the problems qualitatively. The Religious Court in trying a divorce that is caused by the murtad of the husband is based on the principle of Islamic personalization. The Religious Court is in the authority to try someone that has converted his religious. The legal considerations of the Judge in announcing this case is that the religious conversion in a marriage will result in inharmonious household. The legal child from the marriage; they will not have heir inheritance relationship with the father who has converted his religion, which is in accordance with the stipulations in Article 173 of KHI (Compilation of Islamic Laws) about Inhertance Hindrance. Keywords: Authority of Religious Court, Divorce, Murtad (Religious Conversion)